Rapid antiretroviral therapy and treatment outcomes among people living with HIV: exploring the mediating roles of medication adherence - Chen, Hao; Tao, Ran; Wu, Lingli; Chen, Cheng; He, Jingchun (Frontiers in Public Health, 2024)
The rapid initiation of antiretroviral therapy (ART) and its impact on treatment outcomes have been a subject of global public health interest. However, the precise mechanisms underlying the effects of rapid ART initiation remain unclear. This retrospective cohort study examined data from 1846 HIV-infected individuals in Jiulongpo District, Chongqing, China, spanning from 2016 to 2022. Through logistic regression models and serial mediation analysis, the study aimed to explore the influence of rapid ART initiation on treatment outcomes and the role of medication adherence as a mediating factor. The findings revealed a significant association between rapid ART initiation and reduced risk of viral failure (adjusted odds ratio [OR] = 0.320, 95% confidence interval [CI] = [0.161, 0.637]), as well as an increased likelihood of improved adherence (adjusted OR = 2.053, 95% CI = [1.226, 3.438]).Furthermore, medication adherence was identified as a partial mediator in the relationship between rapid ART initiation and viral failure, explaining 10.5% of the total effect. In conclusion, rapid initiation of antiretroviral therapy was found to enhance treatment outcomes, emphasizing the importance of early adherence education. The study recommends early initiation of ART coupled with adherence education and psychological counseling for HIV-infected individuals.